1998
DOI: 10.2331/fishsci.64.740
|View full text |Cite
|
Sign up to set email alerts
|

Use of Otolith Microanalysis to Determine Estuarine Migrations of Japanese Sea Bass <i>Lateolabrax japonicus</i> Distributed in Ariake Sea

Abstract: Japanese sea bass Lateolabrax japonicus is a common euryhaline marine fish distributed in eastern Asian coastal waters, of which life history can be characterized by occasional or seasonal entry to freshwater habitats. Otolith microanalysis for Sr:Ca ratio by a wave-length dispersive electron microprobe was utilized to determine life history trajectory of the Japanese sea bass distributed in Ariake Sea. Laboratory-raised sea bass juveniles which were maintained at various constant salinity re gimes and seriall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 6 publications
0
27
0
3
Order By: Relevance
“…The study and use of otoliths for the characterization of diverse aspects of the biology of fishes has been a common practice among researchers, some have used them to characterize the stages and areas where anadromous species growth (Thresher et al 1994, Thorrold et al 1997, Secor et al 1998, or for the determination of age of commercial fish (Radtke 1987, Lecomte 1992, Secor et al 1995. Paxton (2000) give some categories of fish otolith size; Perciformes, have otoliths of small to moderate size 2-5% in SL.…”
Section: Discussionmentioning
confidence: 99%
“…The study and use of otoliths for the characterization of diverse aspects of the biology of fishes has been a common practice among researchers, some have used them to characterize the stages and areas where anadromous species growth (Thresher et al 1994, Thorrold et al 1997, Secor et al 1998, or for the determination of age of commercial fish (Radtke 1987, Lecomte 1992, Secor et al 1995. Paxton (2000) give some categories of fish otolith size; Perciformes, have otoliths of small to moderate size 2-5% in SL.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that upstream migration to the ETM would promote recruitment success of early juveniles. Using microprobe analyses of otolith Sr and Ca, Ohta et al (1997) and Secor et al (1998) detected evidence of ingress into freshwater during early life stages of Japanese temperate bass in the Ariake Sea. Unfortunately, the ingress into brackish water from seawater could not be detected because the otolith Sr/Ca ratio of Japanese temperate bass only falls significantly in otoliths exposed to freshwater (salinity 0; Ohta et al 1997).…”
Section: Abstract: Migration · Stable Isotopes · Estuary · Salinity mentioning
confidence: 99%
“…0.002 indicated salinity conditions above 10 ppt (Secor et al 1998). Assuming that Sr/Ca increases above 0.002 were the resident history of the high salinity area for K. marginata, the maximum growth during spawning migration were estimated as ca.…”
Section: Spawning Migrationmentioning
confidence: 99%